Parliamentary Control Over Public Expenditure in Bangladesh : The Role of Committees - World Bank (Washington, DC, 2013)
This report explores the scope and limits of parliamentary control over public expenditure in Bangladesh. It focuses on the collective method, identifying the role of three financial committees and a sample of four ministerial committees, referred to here as oversight committees, in the scrutiny of public expenditure. The report seeks to compile the specific outputs of these committees for the last few years, find out the implementation status of their decisions and suggest mechanisms which allow for better monitoring of such decisions as well as propose new areas of work for the committees which could improve accountability and transparency of public expenditures. The report is organized into a number of sections. The following section identifies the ground rules for parliamentary surveillance of public expenditure in Bangladesh. The structure and organization of committees and their scope of work have been described in section three. Section four provides a detailed examination of the working of the (sampled) financial and oversight committees; while their actual impact is assessed in section five. The limits of committee influence in comparative context are described in section six. Proposals for reform are given in section seven.